Hubungan Dukungan Orang Tua Dan Efikasi Diri Dengan Motivasi Belajar Siswa Kelas VIII Sekolah Menengah Pertama - Syarifah Mahmuda; Saiful Akhyar Lubis; Nina Siti S Siregar (Mahesa Research Center, 2022)
This study aims to determine the relationship between parental support and self-efficacy with learning motivation of eighth grade students of SMP Shafiyyatul Amaliyyah Medan, with a population of 103 students. The research sample amounted to 26 students. The method used in this research is quantitative method with sampling technique using Random Sampling Technique . The instrument used is a Likert scale model questionnaire. The data collection technique used three scales consisting of the Parental Support, Self-Efficacy and Learning Motivation scales. The analysis technique used is Multiple Regression. Based on the results of the study it was concluded that: 1) there was a significant positive relationship between parental support and learning motivation with a correlation coefficient (rx1y) of 0.698 with p = 0.000, R2 = 0.487 with a contribution of 48.7%. 2) There is a significant positive relationship between self-efficacy and student learning motivation with the results of the correlation coefficient (rx2y) of 0.715 with p = 0.000, R2 = 0.512 with a contribution of 51.2%. 3) There is a significant positive relationship between parental support and self-efficacy with learning motivation, this result is indicated by the linearity coefficient value of F = 16.919 and p = 0.000, p <0.05 and R2 = 0.595, with a contribution of 59.5%. These results indicate that there are still 40.5% contributions from other factors that can affect learning motivation. From these results it can be said that the higher the parental support and self-efficacy, the higher the learning motivation, and conversely the lower the parental support and self-efficacy, the lower the students' learning motivation.